Promoting Boycotted Product: Audience’s Reception Analysis K-Pop Celebrities’ Soft Promotion for Starbucks - Pascarina, Patrisia Amanda; Hartanto, Louisa Christine; Teguh, Monika; Elvina, Felicia Audrey; Hutasoit, Tiffanny Odelia (Mediator: Jurnal Komunikasi, 2025)
This research aims to unveil the audience’s reception of Starbucks's recent K-Pop celebrity endorsement. The movement of boycotting products that support Israel suddenly disappeared when certain K-Pop Idols showed their pictures holding Starbucks cups. Since war broke out in Gaza, social media influencers around the world have called for boycott action against Starbucks’ products. However, K-Pop celebrities were suspected of carrying out soft promotion by uploading photos of themselves holding Starbucks cups, like Jeannie from Blackpink and Super Junior’s Choi Siwon. Using Stuart Hall’s Audience Receptions analysis, this research used FGD to gain idol fans’ perspective on this phenomenon. According to fans, the factor that makes idols agree to promote Starbucks is the contractual relationship between the artist's agency and Starbucks, which requires artists under the agency to upload photos or other forms of soft selling. The impact of this soft promotion includes a decrease in the trust of fans and other brands who want to choose the artist to be their representative, as well as the loss of the opportunity to return to a career as a K-Pop artist. The South Korean government's position with the people of Gaza who are affected by Israeli army atrocities is also being questioned, which could have an impact on decreased interest in their entertainment industry.